Analisis Ketahanan Budaya Islam dalam Tradisi Panjang Mulud di Kota Serang - Siti Nurkholisoh; Umi Sumbulah; Roibin Roibin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Panjang Mulud tradition represents a local celebration of the Prophet Muhammad’s birthday that has developed within the Banten community, particularly in Serang City. This tradition embodies not only religious values but also social and cultural dimensions that reflect the community’s resilience in maintaining Islamic values amid modernization. This study aims to analyze Islamic cultural resilience within the dynamics of the Panjang Mulud tradition using Clifford Geertz’s interpretive anthropology combined with the theory of cultural resilience. The research employed a qualitative descriptive method with an ethnographic model through participant observation, in-depth interviews, and documentation in Tanggul Village, Cimuncang Subdistrict, Serang City. The findings reveal that Serang’s community demonstrates strong cultural flexibility in preserving Islamic values through the negotiation of meanings between religious, social, and economic aspects. The Panjang Mulud tradition continues to transform in form without losing its spiritual essence and functions as a medium for strengthening local Islamic identity that is adaptive and contextual in the modern era.